Inhibitory effect of carvacrol against Alternaria alternata causing goji fruit rot by disrupting the integrity and composition of cell wall - Zhao, Lunaike; Wang, Junjie; Zhang, Huaiyu; Wang, Peng; Wang, Cong; Zhou, Yueli; Li, Huanhuan; Yu, Shukun; Wu, Rina (Frontiers in Microbiology, 2023)
Goji (Lycium barbarum L.) is a widely planted crop in China that is easily infected by the pathogenic fungus Alternaria alternata, which causes rot after harvest. Previous studies showed that carvacrol (CVR) significantly inhibited the mycelial growth of A. alternata in vitro and reduced Alternaria rot in goji fruits in vivo. The present study aimed to explore the antifungal mechanism of CVR against A. alternata. Optical microscopy and calcofluor white (CFW) fluorescence observations showed that CVR affected the cell wall of A. alternata. CVR treatment affected the integrity of the cell wall and the content of substances in the cell wall as measured by alkaline phosphatase (AKP) activity, Fourier transform-infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Chitin and β-1,3-glucan contents in cells decreased after CVR treatment, and the activities of β-glucan synthase and chitin synthase decreased. Transcriptome analysis revealed that CVR treatment affected cell wall-related genes in A. alternata, thereby affecting cell wall growth. Cell wall resistance also decreased with CVR treatment. Collectively, these results suggest that CVR may exert antifungal activity by interfering with cell wall construction, leading to impairment of cell wall permeability and integrity.